2011
DOI: 10.1074/jbc.m111.219212
|View full text |Cite
|
Sign up to set email alerts
|

The T Cell Receptor Triggering Apparatus Is Composed of Monovalent or Monomeric Proteins

Abstract: Understanding the component stoichiometry of the T cell antigen receptor (TCR) triggering apparatus is essential for building realistic models of signal initiation. Recent studies suggesting that the TCR and other signaling-associated proteins are preclustered on resting T cells relied on measurements of the behavior of membrane proteins at interfaces with functionalized glass surfaces. Using fluorescence recovery after photobleaching, we show that, compared with the apical surface, the mobility of TCRs is sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
51
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 48 publications
(56 citation statements)
references
References 57 publications
5
51
0
Order By: Relevance
“…CD4/Lck, CD45 and MHC class II. These proteins have all previously been claimed to form dimers, but gave strong signals for monomers in the TCCD analysis (figure 5a) [46]. The simple organization of the triggering apparatus of the T cell suggested by these studies is shown in figure 5b.…”
Section: Application To T-cell Biologymentioning
confidence: 82%
See 4 more Smart Citations
“…CD4/Lck, CD45 and MHC class II. These proteins have all previously been claimed to form dimers, but gave strong signals for monomers in the TCCD analysis (figure 5a) [46]. The simple organization of the triggering apparatus of the T cell suggested by these studies is shown in figure 5b.…”
Section: Application To T-cell Biologymentioning
confidence: 82%
“…Although BRET requires heterologous protein expression, the luminescence detection mode allows molecular interactions to be studied at nearnative expression levels so that the observations are relevant to the behaviour of the native proteins, which can also be studied directly using the TCCD method. The TCCD measurements discussed above showed with 95% confidence that all analysed proteins are monomeric [46]. When combined with the orthogonal BRET method for which, in the case of the analysis of the TCR, the upper limit on the fraction of oligomers was estimated to be 10 per cent, these two techniques allow us to be confident that these assignments represent the state of the proteins at the cell surface.…”
Section: Application To T-cell Biologymentioning
confidence: 90%
See 3 more Smart Citations